A Quasi-Experimental Study To Assess The Effectiveness Of Puppet Show And Storytelling Methods On Attention Deficit Hyperactive Disorders Among Preschool Children At Selected Schools, Krishnagiri District - R. Mahalakshmi, R. Mahalakshmi; S. Rajalakshmi, S. Rajalakshmi (Journal of Neonatal Surgery, 2025)
This quantitative study investigated the effectiveness of puppet shows and storytelling methods in addressing challenges faced by preschool children with Attention-Deficit/Hyperactivity Disorder (ADHD). Employing a non-randomized two-group research design, the study involved a total of 60 preschool children (ages 2-6 years) diagnosed with ADHD who met the inclusion criteria. Participants were conveniently sampled using a non-probability technique and assigned to either a puppet show intervention group or a storytelling intervention group. The study aimed to compare the impact of these two methods on specific behavioral outcomes associated with ADHD in preschool children. The findings of the research indicated that both puppet shows and storytelling were effective interventions for this population. However, the study concluded that the puppet show method demonstrated a greater positive impact compared to the storytelling method in addressing the challenges associated with ADHD among the preschool children in the study sample. These results suggest that incorporating puppet shows could be a particularly beneficial strategy in early childhood interventions for children with ADHD. Further research with larger and more diverse samples is recommended to validate these findings and explore the specific mechanisms underlying the differential effectiveness of these methods